Analisis Penyusunan Laporan Keuangan Guna Mengembangkan Usaha Mikro,Kecil, dan Menengah (UMKM) dalam Etika Keuangan - Muhammad Ilham fiqri; Novia Grace Christin Limbong; Olivia Sembiring; Rebecca Putri Sihaloho; Rojelita Catrina Simarmata; Serly Sahfitri; Riza Indriani; Hilma Harmen; Gracella Rosnah S Hutagalung (MES Management Journal, 2024)
Micro, small, and medium-sized financial reporting (UMKM) can build confidence and credibility in external actors, such as banks, investors, and governments, so that they can acquire the working capital and investment they need to thrive and thrive. If financial statements exist, they can serve as a "test tool" for accounting functions, but over time, financial reports become the basis for determining or evaluating the financial position of an UMKM. Financial statements can also be used to assess the performance of a UMKM or to measure the ability of the UMKM to meet its obligations in the short and long term.This writing uses qualitative research methods that involve data collection based on in-depth searches of literature and library sources. Data is collected from reports, textbooks, academic journals, and related articles.The preparation of accurate financial statements and in accordance with the principles of financial ethics is an important step in the development of UMKM. With clear and accurate data, business owners can find improvements such as cost management and improved operational efficiency. It helps in better decision-making, which can increase the profitability and sustainability of UMKM. Focus on developing responsible financial management practices, such as prudent use of funds and transparency. UMKM can build a strong and sustainable reputation by paying attention to social and environmental aspects. In order to support business growth and overall progress, the financial reporting process must be continuously improved to comply with the principles of financial ethics.Good reputation and trust are the key to getting extra funding.